Opportunities, Challenges and Ethics of Artificial Intelligence Implementation in Teaching Islamic Religious Education in Public Universities: A Case Study in South Kalimantan - Uswatun Hasanah; Ririn Khairunnisa; Dhia Alfa Della; Taufik Abdullah Attamimi (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2024)
This research presents a comprehensive overview of the opportunities and challenges in the utilization of Artificial Intelligence (AI) to improve the quality of Islamic Religious Education teaching in universities in South Kalimantan. Furthermore, the researcher explores how the ethics of using AI in Islamic Education learning in public universities. The research method used is qualitative with the type of case study. Data collection techniques used observation, interviews, and document studies. The research sample was PAI lecturers at public universities in South Kalimantan. Data analysis techniques using interactive data models. The results showed that the level of understanding of PAI lecturers in South Kalimantan was not very high due to a lack of understanding of the latest digital literacy, there were concerns that the use of AI would conflict with Islamic values and the lack of maximum internet infrastructure in South Kalimantan. This study also shows that AI has great potential in improving the quality of learning. These findings provide important implications for the development of innovative PAI learning models that are relevant to technological developments. This research aims to provide recommendations for PAI curriculum development that integrates AI technology. By identifying the opportunities, challenges and ethics of AI implementation, this research is expected to contribute to designing more effective and engaging learning strategies for students without violating academic integrity and supporting efforts to improve the quality of higher education in Indonesia.